Kaposiform hemangioendothelioma causing intestinal obstruction - Bassel Salman; Jatin Sharma; Austen Knapp; Begum Akay; Donald Gibson (Elsevier, 2018)
A previously healthy toddler with bilious vomiting and erythematous gluteal rash over 2 weeks had intermittent pain, constipation and decreased appetite. All labs were negative with the exception of fecal occult blood. Abdominal x-ray and ultrasound revealed dilated air-filled loops of bowel and partial small bowel obstruction. After persistent worsening abdominal pain and vomiting a CT scan with IV contrast (Fig. 1) suggested small bowel obstruction. Emergent surgery was performed and diagnostic laparoscopy revealed about 61 cm of necrotic bowel causing stricture formation and mesenteric shortening in the distal small bowel. 56 cm of inflamed bowel was resected with end-to-end anastomosis. Final pathology report indicated diffuse intestinal angiomatosis with transmural involvement and focal erosion consistent with KHE (Fig. 2). Presentation is varied, consists of cutaneous lesion, retroperitoneal mass, intestinal obstruction, jaundice, intussusception, or multifocal neoplasms. Complete surgical resection with wide margins is the best therapeutic option and has achieved the best outcomes. If not treated in sufficient time, KHE has a relatively high mortality rate of 30%, with most deaths occurring due to its locally invasive effects [5]. There are limited reports of identifying features of KHE on imaging. Of 165 cases of KHE none were presented in the small bowel [5]. We report the unique case of KHE presenting as a hypervascular mass causing obstruction in the distal small bowel. Although extremely rare, KHE should be considered as a reason for severe GI stricture or obstruction in infants and children in obscure cases and included in the differential.